Perencanaan Pendidikan dalam Perspektif Islam: Sintesis Konsep At-Takhthith dengan Model Perencanaan Pendidikan Modern (Indo-MathEdu Intellectuals Journal, 2025)
Educational planning is a crucial element that determines the success of educational systems in facing global dynamics and technological disruption. This study aims to synthesize the concept of educational planning from an Islamic perspective (at-takhthith) with modern planning models and analyze its challenges in the era of the Independent Curriculum (Kurikulum Merdeka) and digitalization. Using a qualitative approach with a library research method, data were analyzed inductively and thematically from various scientific literatures ranging from 2020 to 2025. The results indicate that planning in Islam is a theological imperative aimed at forming holistic individuals through the integration of faith (IMTAQ) and science-technology (IPTEK). Managerially, planning functions as a directional guide, a tool for efficiency, and a standard for supervision. This study concludes that a participatory or mixed planning model is the most ideal for balancing national macro-policies with school micro-autonomy. However, field implementation still faces structural challenges, particularly in 3-T areas regarding limited digital infrastructure and teacher competency readiness. The research recommends the need to strengthen school principals' digital leadership and the implementation of Data-Based Planning (PBD) to enhance accountability and sustainable educational quality